The Influence of Quality Perception and Lifestyle on the Intention to Purchase Buttonscarves Hijabs - Arini Ramadhani; Didip Diandra; Lingga Yuliana (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2026)
The hijab industry in Indonesia has experienced rapid growth along with the increasing number of Muslim women wearing hijab and the expansion of the modest fashion trend. This condition intensifies competition among hijab brands, encouraging companies to understand the factors influencing consumers’ purchase intentions. This study aims to analyze the effect of Quality perception and lifestyle on purchase intention toward Buttonscarves hijab. This research employs a quantitative approach using a purposive sampling technique. Primary data were collected through an online questionnaire distributed to 100 respondents who have purchased or used Buttonscarves hijab. Data analysis was conducted using Partial Least Squares (PLS) with the assistance of SmartPLS software. The results indicate that Quality perception has a positive and significant effect on purchase intention, while lifestyle does not have a significant effect on purchase intention. These findings suggest that product quality is the primary factor influencing consumers’ intention to purchase premium hijab products. This study provides managerial implications for hijab brands to consistently maintain and improve product quality to enhance consumers’ purchase intentions.